Health-related quality of life and its predictors among epilepsy patients in Ethiopia: Systematic review and meta-analysis - Chilot Kassa Mekonnen; Hailemichael Kindie Abate; Abere Woretaw Azagew; Muluken Chanie Agimas (PLoS ONE, 2025)
Introduction Epilepsy is a common non-communicable neurological disorder associated with recurrent seeding of cerebral neurons or brain cells and episodes of unprovoked seizures with or without loss of consciousness. Although there are studies on the health-related quality of life of epilepsy patients in Ethiopia, there are remarkable variations in the estimates of health-related quality of life. Objectives This systematic review and meta-analysis aimed to determine the pooled effect size of the health-related quality of life of adult epilepsy patients in Ethiopia. Methods Original articles about the health-related quality of life among epilepsy patients in Ethiopia were searched through known and international databases (PubMed, Scopus, and Web of Science) and search engines (Google and Google Scholar). Data were extracted using a standard data extraction checklist developed according to Joanna Briggs Institute (JBI). The I2 statistics were used to identify heterogeneity across studies. Funnel plot asymmetry and Egger’s tests were used to check for publication bias. The STATA version 11 software was employed for statistical analysis to pool the mean scores of health-related quality-of-life. Result A total of 16 cross-sectional studies with a sample size of 5294 took part. The pooled overall mean score of health-related quality of life among epilepsy patients in Ethiopia was 52.82 ± 13.24 [95%CI (46.41, 59.21)], I2 = 100%, p-value <0.001. Besides, the overall pooled mean score of health-related quality of life based on the measuring tools WHO-QOL-BREF, QOLIE-31, and QOLIE-10 was 51.50 ± 11.32 (49.11, 53.90), 59.99 ± 12.67 (52.22, 67.77), and 44.33 ± 21.23 (13.09, 75.57) respectively. Conclusion The least overall pooled mean score of HRQOL was the QOLIE-10 measuring tool epileptic patients’ mean score compared to other health-related quality-of-life measuring tools such as WHOQOL-BREF, and QOLIE-31. Moreover, the least overall pooled mean score of HRQOL using the WHOQOL-BREF was the environmental domain followed by the emotional domain, as compared to all other domains in each measuring tool of health-related quality of life.